ANALISIS PENERAPAN LAPORAN KEUANGAN UMKM BERBASIS STANDAR AKUNTANSI KEUANGAN SAK-EMKM (STUDI KASUS TOKO GROSIR ADIT AHMAD) - Iqlima Amalia Rahayu; Lilis Lasmini; Meliana Puspitasari (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2025)
This research examines the adoption of financial reporting in Micro, Small, and Medium Enterprises (MSMEs) derived from the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK-EMKM), using Toko Grosir Adit Ahmad in Karawang Regency as a case study. The focus on this theme arises from the importance of standardized financial reports in promoting transparency, accountability, and ease of access to financing. This research utilizes a qualitative methodology with a descriptive framework, with data gathered through interviews, field notes, and document reviews. The outcomes reveal that Toko Grosir Adit Ahmad has not fully implemented the provisions of SAK-EMKM. Financial records are still maintained in a simple manner without the complete preparation of income statements and balance sheets. The main inhibiting factors include limited understanding of accounting standards, a shortage of competent human resources, and insufficient support from external parties, such as training and mentoring. Based on these findings, the study suggests the need to improve accounting literacy among MSME actors and to encourage active involvement of the government and relevant institutions in promoting and supporting the broader implementation of SAK-EMKM.